Research on the Application of Swarm Intelligence Algorithms to the Fire Assignment - Yin, Minglou; Pan, Xiaogang; Jiao, Yuanyuan; Li, Zhimeng (International Conference on Big Data and Information Analytics (Online), 2023)
The fire assignment problem is a multi-parameter, multi-constraint NP (non-deterministic polynomial)-complete problem, the swarm intelligence algorithm has an inherent advantage in the solution, especially in the genetic algorithm, ant colony algorithm and particle swarm algorithm is the most representative, but there are still some shortcomings, such as the lack of interpretability and the tendency to fall into local optimization, and this is the direction of the improvement of the strategy to improve the efficiency of the fire assignment, the intelligent decision-making is of great theoretical significance and practical application value.